2023
DOI: 10.1002/ptr.7800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin/turmeric supplementation on obesity indices and adipokines in adults: A grade‐assessed systematic review and dose–response meta‐analysis of randomized controlled trials

Abstract: In the present study, we explored the effect of curcumin/turmeric supplementation on anthropometric indices of obesity, leptin, and adiponectin. We searched PubMed, Scopus, Web of Science, Cochrane Library, and Google Scholar up to August 2022. Randomized clinical trials (RCTs) investigating the impact of curcumin/turmeric on obesity indices and adipokines were included. We applied the Cochrane quality assessment tool to evaluate the risk of bias. The registration number is CRD42022350946. Sixty eligible RCTs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 131 publications
(426 reference statements)
0
6
0
Order By: Relevance
“…(F) Product recovery and clinical efficacy: Even though, the process developed here provides only lower quantities (in milligrams) of curcumin as compared to the traditional procedure which yields larger quantities (in grams), a key demerit associated with purified naked curcumin is that this requires further nano formulation to enhance its solubility and bioavailability. Secondly, in clinical trials that report detectable benefits of curcumin oral consumption, a daily dose of curcumin is administered in the ranges between 500 mg and 2500 mg. 76 However, in a preclinical study with TENVs, a daily dose of 2.5 mg curcumin equivalent TENVs per kg body weight showed significant amelioration of ulcerative colitis. 37 This corresponds to a human dose of 0.2 mg per kg body weight for TENVs (curcumin equivalent) based on allometric scaling.…”
Section: Greenness Profile and Benchmarkingmentioning
confidence: 98%
“…(F) Product recovery and clinical efficacy: Even though, the process developed here provides only lower quantities (in milligrams) of curcumin as compared to the traditional procedure which yields larger quantities (in grams), a key demerit associated with purified naked curcumin is that this requires further nano formulation to enhance its solubility and bioavailability. Secondly, in clinical trials that report detectable benefits of curcumin oral consumption, a daily dose of curcumin is administered in the ranges between 500 mg and 2500 mg. 76 However, in a preclinical study with TENVs, a daily dose of 2.5 mg curcumin equivalent TENVs per kg body weight showed significant amelioration of ulcerative colitis. 37 This corresponds to a human dose of 0.2 mg per kg body weight for TENVs (curcumin equivalent) based on allometric scaling.…”
Section: Greenness Profile and Benchmarkingmentioning
confidence: 98%
“…The finding of a trend to lower adiponectin levels in subjects with colorectal adenomas taking curcumin and anthocyanins compared to placebo is an unexpected result. A comprehensive systematic review and meta-analysis of 60 randomized controlled trials found that curcumin/turmeric supplementation improved anthropometric indices of obesity and increased adiponectin levels in the general population [ 38 ]. Similarly, dietary anthocyanins significantly increase adiponectin levels, according to evidence from a systematic review and meta-analysis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing body of research outcomes suggest that the active compound in turmeric, known as curcumin, may exert beneficial effects in inhibiting the progression of NAFLD. 61 Notably, supplementing turmeric essential oil (TO) to rats with NAHS, resulted in the reduction of lipid weight, a decline in hepatic TG, and the activation of PPAR-α associated with lipid metabolism. These outcomes suggest that TO exerts inhibitory actions on liver fat accumulation in NAHS by enhancing the lipid metabolism.…”
Section: Othersmentioning
confidence: 99%